Making the Case for a “Manufacturing Execution System” for Software Development. - Naedele, Martin; Kazman, Rick; Yuanfang Cai (Communications of the ACM, 2014)
The authors argue the importance of information integration in the software development process. They believe that information integration would help software managers make suboptimal decisions about productivity, quality and resource allocation. Other topics discussed include a model of a manufacturing execution system, advances in software management tools and five scenarios that illustrate the benefits of information integration in software development management.